Perancangan Sistem Informasi Pencatatan Dan Pengarsipan Surat Masuk Serta Surat Keluar Di Dekanat Fakultas Teknik Universitas Sebelas Maret Surakarta - Sunarto Sunarto; Nuur Rochman Naafian; Kresno Ario Tri Wibowo (Politeknik Harapan Bangsa Surakarta, 2022)
ABSTRACTÂ Correspondence activities are still needed and as proof of a valid document. The Faculty of Engineering, Universitas Sebelas Maret Surakarta (UNS) still uses letters to establish communication with outside parties. Good mail management will provide positive benefits for the agency. Considering the function of the letter which is quite important, it is better for the Faculty of Engineering, UNS, to ensure that the letter storage process can be carried out by following the agenda system procedure. Based on this background, the formulation of the problem to be solved in this research is